THE INFLUENCE OF EXPERIENCE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. TELKOM WITEL MAKASSAR - Aswati, Aswati; Sri Andayaningsih; Firman Syah (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to analyze the influence of work experience and motivation on employee performance at PT. Telkom Witel Makassar. The population in this study was 37 permanent employees at PT. Telkom Witel Makassar. And this research uses a saturated sample, the entire population is sampled. This research data was obtained from a questionnaire (primary data). The research results from data processed using SPSS Version 25 statistical calculations, based on partial SPSS output results, research results show that partially the variables of work experience and work motivation have an influence on employee performance. Other results found that the variables work experience and work motivation had a significant effect on employee performance with a significant value for work experience of 0.001 < 0.05 and a significant value for work motivation of 0.000 < 0.05. Work experience and work motivation have a positive and significant effect on employee performance. Therefore, the two independent variables, namely work experience and work motivation, need to be maintained and maximized so that employee performance can be further improved.